Emergency dialysis in neonatal metabolic crises - Daschner, Markus; Schaefer, Franz (Advances in renal replacement therapy, 2017)
Metabolic crises in children with inborn errors of metabolism are caused by the accumulation of neurotoxic metabolites. Rapid elimination of these metabolites is apparently crucial to prevent irreversible neuronal damage; long-term outcome is correlated with the rate of toxin removal during the crisis. The usefulness of different blood purification techniques for removing accumulated neurotoxins is reviewed in this manuscript.